Implementasi Inovasi Belajar Dengan Metode Project Based Learning Pada Materi Konfigurasi Seri Dan Paralel Pada Siswa Kelas IV SD - Nabella, Almanda Dyas; Cindy Putri Widyawati; Isna Rahmawati (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to analyze the impact of innovative implementation of Project Based Learning to Improve knowledge of series and parallel electrical configuration materials in elementary school level IV students. The study approach used is quasi-experimental with pre-test and post-test designs. The population of this study is grade IV students at an elementary school in the Jombor area, Ceper, with a sample of 12 students divided into two groups The instruments used are series and parallel series of material comprehension tests consisting of multiple-choice questions and descriptions. The results showed that there was a significant difference in the improvement of material understanding. Students who were taught with the PJBL model showed an increase in better understanding. This proves that project-based learning innovations have the ability to increase students' knowledge of the concept of series and parallel electrical circuits.